Banking Regulation in Mexico: Lessons From Financial Crises - Karen Sigmond (My University, 2016)
This article first provides a survey of recent Mexican banking his- tory. It then analyzes the causes that led to the peso crisis (1995) and the bank- ing crisis that came after as well as the government response, the bank bailout, and the role of international financial organizations. Regulatory reforms of the Mexican financial system are also discussed. These provide the background for comparative analysis with the financial crisis (2007-2009) that initiated in the United States of America. Both crises are compared and contrasted, both in terms of the causes leading to them and the regulatory responses by the govern- ments. Finally, by studying the similarities and differences, lessons are drawn from both cases.